PENERAPAN MODEL TEAM GAMES TOURNAMENT (TGT) DENGAN MEDIA INTERAKTIF UNTUK MENINGKATKAN MINAT DAN PEMAHAMAN SISWA DALAM MATA PELAJARAN INFORMATIKA DI SMPN 7 MALANG - Saputra, Ismed Eko Hadi; Irianto, Wahyu Sakti Gunawan; Wardhana, Nyoman Dedi Kusuma; Hermansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This project aims to increase student engagement and understanding of informatics subjects at SMPN 7 Malang by using the Team Games Tournament (TGT) learning model with interactive media. Thirty eighth grade students participated in two cycles of Classroom Action Research (PTK). Interest questionnaires and comprehension tests (pre-test and post-test) were used to collect data. Compared to Cycle 1, when the N-Gain was 0.38 (medium), Cycle 2 had an N-Gain of 0.62 (high), and the learning completeness increased from 51.85% to 92.59%. Even the level of interest in learning increased, from a moderately high 80.46% to a very high 92.22%. These results show that when TGT is combined with interactive media, it can provide interesting and relevant learning. One of the pedagogical consequences is the need to provide training to teachers on how to develop collaborative learning experiences involving technology.